“Eyes wide shut”: Paul Ricoeur’s Biblical Hermeneutics and the Course of Recognition in John Milton’s Paradise Lost - Grzegorzewska, Małgorzata (Text Matters: A Journal of Literature, Theory and Culture, 2014)
The author of the paper analyzes John Milton’s great epic narrative through the lenses of Paul Ricoeur’s biblical hermeneutics and his philosophical reflection, in particular the second chapter of the philosopher’s last book, Parcours de la Reconnaissance (The Course of Recognition), devoted mainly to the prospects and pitfalls of recognizing oneself. Two excerpts from St. Paul’s Letter to Romans (14:23b) and the Letter to Corinthians (1, 13:12) highlight the main points of reference in this argument: (1) the concept of involuntary wrongdoing and (2) the contrast between the present opacity and the projected transparency of the knowing subject, connected with the promise of seeing face-to-face, whose fulfilment is rooted in God’s antecedent knowledge of a human being. It is argued that Ricoeur’s focus on the precarious fate of the “fallible man” and his simultaneous desire to outline the destiny of the “capable man” elucidate Milton’s masterpiece evocations of the Aristotelian anagnorisis in Paradise Lost.